Creative innovations for the sustainable city: Widening the range of the possible - Voula P. Mega (Fondazione Eni Enrico Mattei (FEEM), 1997)
Europe is first and foremost urban. In the 1990s, cities emerge stronger on the European scene; they wish to become attractive to people and capital. Winning the battle of sustainability is central to this effort, and presupposes a thorough understanding of this frequently used term, with environmental, economic, social and cultural dimensions. The European Foundation's project on innovations conducive to the sustainable city, which this paper analyses, involved an examination of innovative projects in cities of all European Union states. Projects highlighting the environmental dimensions of sustainability include the local movements for environmental plans, charters and Agendas 21, the development of co-generation and heating schemes, innovative types of resource (including waste) management, and actions to limit the use of the private car and enhance public transport. Projects focusing on socio-economic sustainability aim at improving the employment outlook, housing situation and safety conditions of cities. Planning interventions target bringing harmony to cities, improving the mix of uses and functions (in contrast to rigid zoning) linking the city with its periphery and enhancing public spaces as centres of citizenship and democracy.
Keywords: 330; Innovation; Stadtentwicklung; Nachhaltige Entwicklung; EU-Staaten